Impulsive Rats Exhibit Blunted Dopamine Release Dynamics during a Delay Discounting Task Independent of Cocaine History - Moschak, Travis M. (eNeuro, 2017)
The inability to wait for a large, delayed reward when faced with a small, immediate one, known as delay discounting, has been implicated in a number of disorders including substance abuse. Individual differences in impulsivity on the delay discounting task are reflected in differences in neural function, including in the nucleus accumbens (NAc) core. We examined the role of a history of cocaine self-administration, as well as individual differences in impulsivity, on rapid dopamine (DA) release dynamics in the NAc core. Rats with a history of cocaine or water/saline self-administration were tested on delay discounting while being simultaneously assayed for rapid DA release using electrochemical methods. In controls, we found that cue DA release was modulated by reward delay and magnitude, consistent with prior reports. A history of cocaine had no effect on either delay discounting or DA release dynamics. Nonetheless, independent of drug history, individual differences in impulsivity were related to DA release in the NAc core. First, high impulsive animals exhibited dampened cue DA release during the delay discounting task. Second, reward delay and magnitude in high impulsive animals failed to robustly modulate changes in cue DA release. Importantly, these two DAergic mechanisms were uncorrelated with each other and, together, accounted for a high degree of variance in impulsive behavior. Collectively, these findings demonstrate two distinct mechanisms by which rapid DA signaling may influence impulsivity, and illustrate the importance of NAc core DA release dynamics in impulsive behavior.